Magnetic and structural studies of Fe3O4 nanoparticles synthesized via coprecipitation and dispersed in different surfactants. Issue 13 (September 2017) - Arévalo, P.; Isasi, J.; Caballero, A.C.; Marco, J.F.; Martín-Hernández, F.
Abstract: We present a study of the structural characteristics and magnetic behavior of Fe3 O4 nanoparticles synthesized via coprecipitation and dispersed in different surfactants, among which we include acid oleic acid (OA), sodiumdodecylsulfate (SDS), polyvinyl alcohol (PVA) and several olive oils with different acidity, especially 0.2° (O2) and 1.0° (O10). The obtained samples were characterized by thermal analysis, X-ray diffraction, transmission electron microscopy (TEM), Fourier transform infrared (FTIR) and Mössbauer spectroscopies as well as M vs. H measurements. X-ray diffraction shows single phases having cubic spinel crystal structure whose crystallite size ranges between 9.4–11.1 nm. These results are in good agreement with TEM images also revealing the existence of an organic shell around the Fe3 O4 nanoparticles, more visible for olive oils and insignificant in the sample dispersed with SDS. FTIR spectra of all synthetized samples show the two main broad metal-oxygen bands corresponding to intrinsic stretching vibrations of the metal located in tetrahedral and octahedral sites and additional sets of bands due to the different organic chains of surfactants. Mössbauer data indicated non-stoichiometric magnetite for Fe3 O4 -AO, Fe3 O4 -O2/O10 and Fe3 O4 -PVA samples and a large presence of maghemite for Fe3 O4 -SDS sample. All the obtained samples present superparamagnetic behavior, finding the greatest magnetization for Fe3 O4 -AO. Olive oils show comparable results than oleic acid, confirming their suitability as coating agents for this kind of synthesis.